Occupational stress contributes to the job performance / Faridah Hanim Ismail, Faradewi Bee Abdul Rahman and Suriati Osman - Ismail, Faridah Hanim; Abdul Rahman, Faradewi Bee; Osman, Suriati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The job stress is very prominent that always happens in any organisation or company nowadays. Many factors lead to job stress, such as personal problems, financial, low salary, and others. These factors can affect employees' productivity, commitment, and professionalism to perform their task. The workforce of a hotel plays an important role in satisfying a customer. A survey was distributed to 50 food and beverage staff using a convenient sampling approach via drop and collect method, at Anantara Desaru Coast Resort and Villas. The data was analysed by using Statistical Package for Social Science (SPSS) version 26. Based on the findings, all the independent variables have a significant association with job performance. Nevertheless, from the analysis of multiple linear regression, the results showed that time pressure and skill discretion significantly correlated to predict job performance.